Contextualizing traditional water knowledge with modern water challenges in India: A hydrological review (Indian Journal of Traditional Knowledge (IJTK), 2025)
During last few decades many new challenges in the field of water have emerged such as impacts of climate change, declining groundwater levels, decline in groundwater recharge, water logging, encroachment of water sources, decline in green cover, increasing menace of flood and silting due to encroachment of floodplain of rivers, increasing water pollution due to inappropriate and inadequate disposal of solid and liquid wastes, cloudburst, flash flood, cyclone and other disasters, etc. Due to increasing water demand and decreasing water availability, ensuring water security has emerged as a big challenge. India is a unique country where rivers are worshiped and respected since ancient times. Evidences are available in ancient scriptures about hydrological knowledge and importance of water management. Various traditional systems of water harvesting, conservation and management are still available and some are being used since ancient times. In spite of this traditional knowledge and cultural values, the water resources of India are in turmoil due to rapid industrialization, urbanization and materialistic approach towards over-exploitation of natural resources. This paper attempts to contextualize Indian traditional water knowledge with contemporary water challenges in India. Such traditional structures and knowledge, if adopted and practiced prudently, can provide sustainable solutions even today.